Enrichment of Heavy Metals in Sediments as Pollution Indicators of the Aquatic Ecosystem (Biological Sciences - PJSIR, 2007)
. The sedi111ent poll utant status of twenty three communities(villages) w ithin the llaje l ocal govem111ent area of Ondo state, Nigeria, was exa111ined. These are co111111unities , where oil spillage had occurred. Three other location s at lgbokod a were equally considered as a reference point. Ni ne heavy 111etal s; copper (Cu),cadmiu111 (Cd),cobalt (Co),iron (Fe),chromiu111 (Cr),nickel (N i),l ead (Pb), zinc (Zn) and manganese (Mn) were dete1111ined in th e sediments collected from the various co111111unitie s. The lowest concentrations were observed with Co and Zn ranging fro111 0. 1 1 to 0.82 mg/kg and 0.02 to 0.29 111g/kg respective ly, while Co and Fe were at the h ighest concentration s rangi ng fro111 I 004 to 2879 mg/kg and 806 to 3809 mg/kg respectively. Most of the metals in this stud y occur at concentration that cal l s for seriou s environ111ent al concern especially for the water and its resources. Local differences were equally observed in relation to the depth of the ocean . Some of the 111etal controlli ng factors such as pH , organic carbon, and cations exchange capacity were implicitl y considered and each was found to correlate respecti vely, with the 111etal s examined. The results provided relevant bench111ark s for addressin g the protection of benthic organis111s and for assessi ng the potential i111pact of sediment-associated chemical (heavy metals) on aquatic biota. The positi ve correlations as being displ ayed by some of the metals are indicative of similar source of poll utants.